SysML and UML models usage in Knowledge Based MDA process - Butleris, Rimantas; Lopata, Audrius; Ambraziunas, Martas; Veitaitė, Ilona; Masteika, Saulius (Elektronika ir Elektrotechnika, 2015)
The article presents Enterprise Model generation process from SysML models of four types (Use Case, Activity, Block Definitionand Requirements) as well as Knowledge Based MDA tool’s prototype which isimplementing the defined algorithms. In the article defined SysML models parsing algorithms use the recursive data processing approach due to complex UML models structure.The algorithms description is presented as Activity diagrams and explained in tables, where are depicted basics steps and actors as well as the output results. Knowledge Based MDA tool’s prototype currently is capable of processing Use Case and Activity models. Prototype is implemented using three layers (GUI,Logic and Data) architecture. The detailed architecture is presented and described in this article using class diagrams. The prototype is implemented using .Net frameworkand C# programming language. DOI: http://dx.doi.org/10.5755/j01.eee.21.2.5629